Perbandingan Fikih tentang Gharar : Analisis Praktik Gharar dalam Transaksi Ekonomi Islam - Jalaluddin, Jalaluddin (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
One of the rules of fiqhiyah states that a transaction can be corrupted if there are many things that cannot be known before the transaction is carried out, but not if the transaction is only slightly entered. In this case, the author wants to consider the criteria for a contract to be considered corrupt, and explain the types of gharar that are prohibited and the types of gharar that are allowed based on the description of the rule. The method used in this article is literature research with descriptive analysis. The result is that gharar is permissible if the gharar is considered small. The way to find out the small size of the gharar that occurs is gharar that has become a common habit where if in a transaction there is a small amount of gharar that has been accepted as part of the market tradition, then it is considered normal by people and no party feels disadvantaged.